Liberal Culturalism and the National Minority/Immigrant Dichotomy - Lu, Catherine (Les ateliers de l'éthique / The Ethics Forum, 2015)
Is the discrepancy between the cultural and linguistic rights of immigrants on the one hand and national groups on the other justified, with the latter group typically enjoying a fuller set of such rights than the former category? Patten presents a case for accepting some modest departures from neutrality in the treatment of immigrants’ cultural rights and that of majority and minority national groups. I challenge his thesis by asking whether such departures are justified with respect to already settled (as opposed to prospective) immigrants; whether the situational argument for unequal treatment is inconsistent with the theory of culture offered earlier in the book; and whether contexts of historical injustice against immigrant groups might complicate judgements about the national minority/immigrant dichotomy with respect to minority cultural rights.